The Process of Making Balinese Loloh Cemcem Drinks as Biology Learning Materials on the Topic of Natural Ingredients and Active Compounds in Plants - Septian Cahya Azhari; I Nyoman Suardana; Cornelia Wening Manggalagita; Elisa Magdalena Br Gultom (Jurnal Pendidikan dan Pembelajaran Sains Indonesia (JPPSI), 2023)
Cemcem leaves (Alstonia scholaris (L.)) are the basic ingredient in making the traditional herbal drink loloh cemcem. Loloh cemcem has good bioactive ingredients to increase endurance and traditional medicine to prevent and treat various diseases. This study used an exploratory qualitative approach, which aims to explain the process of making the traditional herbal drink loloh cemcem which is useful for biology learning material on the topic of natural ingredients and active compounds in plants and explores the value of local wisdom in the manufacturing process. The data source in this study used purposive sampling with two loloh drink producers cemcem located in Penglipuran Traditional Village, Bangli Regency, Bali Province. The data in this study were obtained through interview techniques, observation, documentation, and literature study. The results showed that the process of making loloh cemcem drink was divided into three phases, first processing cemcem leaves, young coconut, palm sugar, tamarind, and red chili, the second is to pack the loloh into an airtight bottle and the third to put the loloh in the refrigerator. The value of local wisdom in making loloh is that the materials used are 100% still natural, and the manufacturing process is traditional. Generally, parents are the producers of loloh; there is cooperation in making loloh, and public knowledge about the efficacy of loloh cemcem is a legacy from the ancestors of the Balinese people.